DIGITAL MARKETING: INSTAGRAM SEBAGAI MEDIA PEMASARAN PRODUK UMKM - Tasyabila, Happy; Damayanti, Damayanti; Aprilia, Hani Damayanti (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
This study aims to determine the implementation of digital marketing as a marketing medium for MSME products. This research is a descriptive research with a qualitative approach. The location of this research is Respiesusu MSME in Bandar Lampung City. Collecting data using observation techniques, interviews, and documentation. Informants were determined using purposive sampling and snowball sampling methods. Data were analyzed using an interactive analysis model by means of data collection, data reduction, data display, and drawing conclusions. The results of the study show that Respiesusu applies 6 digital marketing processes and digital channels used for the marketing process via Instagram. 6 digital marketing processes carried out by Respiesusu namely Accessibility: endorse, paid promote, regularly upload photos; videos; and e-flyers, using hashtags, and ease of transaction processing. Interactivity: holding sharing activities and providing the best service. Entertainment: create promotional content that follows trends, provides discounted promos, and give aways. Trust: analyze market needs to display complete and trustworthy advertisements. Interruptions: difficulties in the video editing process, signal network disturbances, and server downtime. Informative: share product information through photos; videos; and e-flyers, providing complete product descriptions and an attractive language style.